ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL PEMBERIAN KREDIT USAHA KECIL MENENGAH PADA PT. BANK TABUNGAN NEGARA CABANG TERNATE - Primagama, Mulyati; Nangoi, Grace B.; Runtu, Treesje (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
In granting loans bank has a risk of bad credit. Internal control is the methods used to coordinate a company to achieve the corporate goals which include organizational structure division of authority, established procedures, and healthy practices. this is done to minimize the risk of bad credit. Banks must be able to detect bad loans first so as not to cause bank losses. The direction of this research is to find out the application of internal control based on credit at PT. Bank Tabungan Negara Ternate. The research method used in this research is a qualitative method. The results of research related to the internal receivable control system has been carried out well in accordance with the elements of internal control of COSO including the control environment, risk assessment, control activities, information and communication, monitoring.Keywords: Internal Control,Â Granting Credit